IMPROVEMENT OF TECHNOLOGICAL PROCESSES FOR INSTALLING ANCHOR BOLTS ON ACRYLIC COMPOSITIONS DURING THE INSTALLATION AND ASSEMBLY OF EQUIPMENT AND PRODUCTION LINES - Zolotova, N.; Suprun, O. (Municipal economy of cities. Series: «Economy science», 2024)
The article discusses and improves the technological processes of installing anchor bolts on acrylic compositions during the installation of technological equipment at industrial enterprises in Ukraine, the optimal acrylic compositions developed at the O.M. Beketov National University of Urban Economy in Kharkiv and shows the relevance of using such compounds.